Induction of endoplasmic reticulum stress and inhibition of colon carcinogenesis by the anti-helmintic drug rafoxanide. (10th October 2019) - Laudisi, Federica; Di Grazia, Antonio; De Simone, Veronica; Cherubini, Fabio; Colantoni, Alfredo; Ortenzi, Angela; Franzè, Eleonora; Dinallo, Vincenzo; Di Fusco, Davide; Monteleone, Ivan; Fearon, Eric R.; Monteleone, Giovanni; et al.
Abstract: Colorectal cancer (CRC) remains one of the leading causes of mortality worldwide. Drug repositioning is a promising approach for new cancer therapies, as it provides the opportunity to rapidly advance potentially promising agents into clinical trials. The FDA-approved anti-helminthic drug rafoxanide was recently reported to antagonize the oncogenic function of the BRAF V600E mutant protein, commonly found in CRCs, as well as to inhibit the proliferation of skin cancer cells. These observations prompted us to investigate the potential anti-cancer effects of rafoxanide in CRC models. We found rafoxanide inhibited proliferation in CRC cells, but not in normal colonic epithelial cells. Rafoxanide's anti-proliferative action was associated with marked reduction in cyclin D1 protein levels and accumulation of cells in the G0/G1 phase. These effects relied on selective induction of the endoplasmic reticulum stress (ERS) response in CRC cells and were followed by caspase-dependent cell death. Systemic administration of rafoxanide to Apc m in /+ mice induced to develop CRCs caused ERS activation, proliferation inhibition and apoptosis induction in the neoplastic cells. Collectively, our data suggest rafoxanide might be repurposed as an anti-cancer drug for the treatment of CRC. Highlights: The anti-helmintic agent rafoxanide is a powerful inhibitor of CRC cell proliferation and survival in vitro and in vivo . Rafoxanide showed preferential activity on CRC cells relative to normal colon epithelial cells in vitro and in vivo . Rafoxanide negatively affects CRC cell growth through the induction of endoplasmic reticulum stress response. The rafoxanide-induced anti-mitogenic action on CRC cells was followed by caspase-dependent cell death.